2012
DOI: 10.2105/ajph.2012.300966
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Over-the-Counter Emergency Contraception in 2 Disparate New York City Neighborhoods

Abstract: We conducted a telephone survey of pharmacies in 2 New York City neighborhoods on same-day availability, type, and cost of over-the-counter emergency contraception. There was no difference in availability of over-the-counter emergency contraception between Upper East Side and East Harlem pharmacies (93% vs 94%; P = .71). Average cost of medication was less in East Harlem than in the Upper East Side ($45.16 vs $51.64; P < .001). Efforts should accentuate overcoming cost and knowledge barriers associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Other recent studies have examined EC availability and access utilizing mystery callers and shoppers, including male consumers [7,[15][16][17][18][19][20]. These studies have also shown that although EC is available, accessibility is not guaranteed.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies have examined EC availability and access utilizing mystery callers and shoppers, including male consumers [7,[15][16][17][18][19][20]. These studies have also shown that although EC is available, accessibility is not guaranteed.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that access to EC in New York City is very good, regardless of socioeconomic factors. 14…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that access to EC in New York City is very good, regardless of socioeconomic factors. 14 Misinformation on legal age of OTC EC purchase is concerning. In all, 62% provided correct information regarding age in 2009 compared to only 53.2% in 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Brant et al also used this method to identify gaps in pharmacist knowledge in Massachusetts, USA about ulipristal acetate (Brant et al, 2014), and Bullock noted a similar unfamiliarity with ulipristal acetate among pharmacists in Hawaii (Bullock et al, 2015). Legare noted the homogeneity of availability of EHC in different New York neighbourhoods (Legare et al, 2012).…”
Section: 'Mystery Shopping' For Ehc At Pharmaciesmentioning
confidence: 99%